Effects of season and GA3 concentrations on Hylocereus undatus flowering and production - Takata, William Hiroshi Suekane; Miyake, Rodrigo Takashi Maruki; Narita, Nobuyoshi; Ono, Elizabeth Orika [UNESP] (Science Alert, 2016)
Background: The exotic fruit market in Brazil has gained prestige and cultivation of pitaya is promising. But the cycle is limited throughout the year and its flowering by photoperiod. Methodology: The plant growth regulator use especially gibberellin can replace the need for long days in this sense, it was studied different application periods and various GA concentrations in non-inductive period in order to anticipate flowering. Results: The experimental design was randomized blocks in factorial scheme 3×5, being 3 times of application and five concentrations of the plant growth regulator. The application periods began in May, June and July and it was applied 3 times, one every 30 days. The concentrations studied were (0, 100, 200, 300 and 400 mg L-1 of GA3). Application season did not influence any of the traits, on the other hand, the concentration factor, despite of not having anticipated the flowering but increased fruit set, fruit number, average fruit mass and productivity. Conclusion: Based on the results, it was concluded that the GA3 application was beneficial to the pitaya’s agronomic characteristics.
Keywords: Fruit set; Gibberellin; Pitaya; Plant growth regulator